Accessibility in the elementary schools of a municipality west of Sao Paulo - Medice, Jose; Frigieri de Vitta, Fabiana Cristina [UNESP]; Souza de Conti, Marta Helena; Zaniolo, Leandro Osni [UNESP]; De Vitta, Alberto (Cuba Editora, 2015)
This study aimed to identify and describe the architectural barriers in elementary schools, before and after the Law of Guidelines and Bases (LDB). It is a cross-sectional, descriptive research to map the architectural conditions of access in fourteen elementary schools in the municipal schools network in a medium-sized city in the western region of the state of Sao Paulo. The environments were visited and data collection was performed using a standardized protocol. Data was compared to those established by ABNT-9050 and categorized into appropriate and inappropriate. It was observed that 100% of schools before and after LDB, had no anti-slip flooring, tactile warning and directional; accesses, ramps and stairs had no guides and guideposts; dimensions, grip and slip handrails were inadequate, the toilets had no transition area, mirrors and sinks were not adapted; there was no outside furniture such as drinkers and tailored service counters and adapted libraries. Therefore, this study also has shown that schools installed, pre and post LDB presented several inappropriate items to the ABNT (Brazilian Association of Technical Standards) standards.
Keywords: Accessibility; Schools; Architectural Barriers